Communication Styles Among Members of Student Organizations in Indonesian Universities - Mila Umil Habibah; Erna Iftanti (Asshika: Journal of English Language Teaching & Learning, 2024)
The article examines the dominant communication styles utilized by student organization members and their impact on organizational effectiveness. This means that the way of conveying opinions or information, commonly known as communication style, can influence an individual's perspective in understanding information  The research employs mixed method, use descriptive quantitative and qualitative method, primarily focusing on data collected through surveys and interview administered to students across several Indonesian universities. This method allows for a comprehensive analysis of the dominant communication styles, including Equalitarian, Structuring, and others, as well as the factors influencing their use. . Therefore, the purpose this article is to analyze the dominant communication styles used by student organization members, both when expressing opinions and when carrying out work programs, which certainly influence their actions and thinking patterns about certain ideas or opinions. The results indicate that the Equalitarian Style is the most dominant communication approach among student organization members. This style promotes an inclusive environment where all members feel empowered to express their opinions and contribute to discussions, ultimately enhancing collaboration and mutual understanding. The findings suggest that adopting an Equalitarian communication style significantly improves organizational effectiveness by fostering a culture of openness and respect among members.